The Integration of Nahwu Science and Tasawwuf Moral Education in the Book of Nahwu Al-Qulub by Imam Qusyairi for Arabic Language Learning - Rahman, Miftahur (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to explore the specific learning needs of students seeking to enhance the quality of human resources through a combined approach that integrates Nahwu Science with the moral teachings of Tasawwuf. The research objectives are multi-fold: firstly, to examine the systematic structure of topics addressed in Nahwu al-Qulub by Shaykh Imam Qushayri; secondly, to identify the moral values embedded within Tasawwuf as presented in the text; and thirdly, to investigate the integration of Nahwu Science with Tasawwuf's ethical education within Nahwu al-Qulub by Shaykh Imam QushayriThe research employs a qualitative approach, utilising a descriptive analysis method, while adopting a library research (or literature study) design. This approach involves gathering and examining materials pertinent to the discussion's theme and the issues raised, with sources drawn exclusively from literature. The analysis commences post-data classification, a process that transforms raw data into actionable insights, thereby enabling the identification of interconnections between various data points. The findings of this study reveal several key insights. Firstly, the systematic exposition of concepts within Nahwu al-Qulub by Imam al-Qushayri is consistent with the traditional structure of classical Nahwu. The text begins with a discussion of "al-Kalam" and proceeds through an examination of Isim, Fi'il, and Harf terminologies. Nahwu al-Qulub itself appears at a pivotal phase in the development of Nahwu, one marked by maturation and refinement, aligning with the periodisation suggested by scholars such as Syauqi Dhaif and al-Tantawi. Secondly, the study identifies core moral values of Sufism within the work, including an educational perspective that regards human beings holistically, addressing both divine and human dimensions, with the ultimate aim of fostering closeness to the Creator, al-Haqq, and cultivating self-awareness. Lastly, this research unveils an integration of Nahwu science with Sufi ethics, classifying Sufism’s dimensions into three key stages: Takhalli (purification), Tahalli (embellishment), and Tajalli (illumination).